Metabolic subtypes of patients with NAFLD exhibit distinctive cardiovascular risk profiles. Issue 4 (17th March 2022) - Martínez‐Arranz, Ibon; Bruzzone, Chiara; Noureddin, Mazen; Gil‐Redondo, Ruben; Mincholé, Itziar; Bizkarguenaga, Maider; Arretxe, Enara; Iruarrizaga‐Lejarreta, Marta; Fernández‐Ramos, David; Lopitz‐Otsoa, Fernando; Mayo, Rebeca; Embade, Nieves; et al.
Abstract: Background and Aims: We previously identified subsets of patients with NAFLD with different metabolic phenotypes. Here we align metabolomic signatures with cardiovascular disease (CVD) and genetic risk factors. Approach and Results: We analyzed serum metabolome from 1154 individuals with biopsy‐proven NAFLD, and from four mouse models of NAFLD with impaired VLDL‐triglyceride (TG) secretion, and one with normal VLDL‐TG secretion. We identified three metabolic subtypes: A (47%), B (27%), and C (26%). Subtype A phenocopied the metabolome of mice with impaired VLDL‐TG secretion; subtype C phenocopied the metabolome of mice with normal VLDL‐TG; and subtype B showed an intermediate signature. The percent of patients with NASH and fibrosis was comparable among subtypes, although subtypes B and C exhibited higher liver enzymes. Serum VLDL‐TG levels and secretion rate were lower among subtype A compared with subtypes B and C. Subtype A VLDL‐TG and VLDL–apolipoprotein B concentrations were independent of steatosis, whereas subtypes B and C showed an association with these parameters. Serum TG, cholesterol, VLDL, small dense LDL5, 6, and remnant lipoprotein cholesterol were lower among subtype A compared with subtypes B and C. The 10‐year high risk of CVD, measured with the Framingham risk score, and the frequency of patatin‐like phospholipase domain‐containing protein 3 NAFLD risk allele were lower in subtype A. Conclusions: Metabolomic signatures identify three NAFLD subgroups, independent of histological disease severity. These signatures align with known CVD and genetic risk factors, with subtype A exhibiting a lower CVD risk profile. This may account for the variation in hepatic versus cardiovascular outcomes, offering clinically relevant risk stratification.